2005
DOI: 10.1029/2005gl023504
|View full text |Cite
|
Sign up to set email alerts
|

In situ timing and pointing verification of the ICESat altimeter using a ground‐based system

Abstract: [1] To provide validation of the ICESat laser altimeter time of measurement and geolocation, a ground-based technique was implemented at White Sands Space Harbor (WSSH), during the Laser 2a and 3a operational periods. The activities used an electro-optical detection system and a passive array of corner cube retro reflectors (CCR). The detectors and the CCRs were designed to provide an independent assessment of the laser footprint location, while the detectors also provide timing verification. This groundbased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…The aerophotogrammetric DEM and ICESat (DI ) resulted in the smallest shift vector (≈3 m) and an RMSE (3.6 m) of stable terrain after two iterations. We expect the aerophotogrammetric DEM to be of the highest quality and accuracy, thus the impressive coherence with ICESat further confirms previously published ICESat horizontal and vertical accuracies (Fricker et al, 2005;Luthcke et al, 2005;Magruder et al, 2005;Shuman et al, 2006;Brenner et al, 2007). For the other 5 comparisons, the SPOT5-HRS DEM compared better than the ASTER, with a shift vector Before After Fig.…”
Section: Universal Co-registration Correctionsupporting
confidence: 71%
“…The aerophotogrammetric DEM and ICESat (DI ) resulted in the smallest shift vector (≈3 m) and an RMSE (3.6 m) of stable terrain after two iterations. We expect the aerophotogrammetric DEM to be of the highest quality and accuracy, thus the impressive coherence with ICESat further confirms previously published ICESat horizontal and vertical accuracies (Fricker et al, 2005;Luthcke et al, 2005;Magruder et al, 2005;Shuman et al, 2006;Brenner et al, 2007). For the other 5 comparisons, the SPOT5-HRS DEM compared better than the ASTER, with a shift vector Before After Fig.…”
Section: Universal Co-registration Correctionsupporting
confidence: 71%
“…The results show the range errors from frequency change are <1 cm [ Sun et al , 2004]. The accuracy of the GLAS measurement time stamps has been evaluated by registering the arrival time of laser pulses from GLAS at a ground based detector array [ Magruder et al , 2005] and the errors were found to be <3 usec.…”
Section: On‐orbit Science Measurementsmentioning
confidence: 99%
“…For validation, we assume that both the GLAS range measurement and its pointing direction may be in error but that the orbital position has negligible error, based on state of the art orbit estimation [ Schutz et al , 2005]. Data time tags have been validated to a few microseconds [ Magruder et al , 2005] and are also a negligible error source. To validate both range and pointing throughout the satellite lifetime, GLAS measurements are required over independently‐surveyed, unchanging topography for which a change in pointing produces a change in range.…”
Section: Introductionmentioning
confidence: 99%